Strengthening Sharia Economic Law in Indonesia: Challenges and Strategic Approaches Amidst Global Economic Dominance - Musthofa, Adinda Yuliana; Afif, Fayiz; Karimuddin, Karimuddin (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
In the current context of economic globalization, Indonesia's Sharia-based economic system faces significant challenges in developing itself amidst the dominance of capitalist and socialist economic systems. This article aims to analyze the challenges faced by Indonesia's Sharia-based economic system and explore the maslahah mursalah approach as a conceptual framework to address these challenges. Through this approach, the article presents several strategic steps to strengthen the position of Sharia economics in Indonesia, including efforts to maintain the identity of Sharia economic law in a global environment dominated by capitalism, gathering empirical evidence on the advantages of Sharia economics, and increasing dialogue and collaboration between the academic community and practitioners of Sharia economics. This study fills the research gap by providing empirical comparative studies on the advantages of Sharia economics over capitalist and socialist systems, offering strategic solutions for practical implementation, and emphasizing the importance of academic-practitioner collaboration. This research's novelty is applying the maslahah mursalah conceptual framework, strategically reinforcing Sharia economic law identity, and enhancing academic-practitioner interaction. This article contributes to understanding the potential and challenges of developing Sharia economic law in Indonesia, offering new perspectives and concrete steps to strengthen Sharia economics in a dynamic global context. The findings enrich theoretical discussions and provide practical solutions to bolster the Sharia-based economic system amidst the prevailing global economic paradigms.